Global meta-analysis shows action is needed to halt genetic diversity loss - Robyn E. Shaw; Katherine A. Farquharson; Michael W. Bruford; David J. Coates; Carole P. Elliott; Joachim Mergeay; Kym M. Ottewell; Gernot Segelbacher; Sean Hoban; Christina Hvilsom; Sílvia Pérez-Espona; Dainis Ruņģis; et al. (Nature, 2025)
Abstract Mitigating loss of genetic diversity is a major global biodiversity challenge1–4. To meet recent international commitments to maintain genetic diversity within species5,6, we need to understand relationships between threats, conservation management and genetic diversity change. Here we conduct a global analysis of genetic diversity change via meta-analysis of all available temporal measures of genetic diversity from more than three decades of research. We show that within-population genetic diversity is being lost over timescales likely to have been impacted by human activities, and that some conservation actions may mitigate this loss. Our dataset includes 628 species (animals, plants, fungi and chromists) across all terrestrial and most marine realms on Earth. Threats impacted two-thirds of the populations that we analysed, and less than half of the populations analysed received conservation management. Genetic diversity loss occurs globally and is a realistic prediction for many species, especially birds and mammals, in the face of threats such as land use change, disease, abiotic natural phenomena and harvesting or harassment. Conservation strategies designed to improve environmental conditions, increase population growth rates and introduce new individuals (for example, restoring connectivity or performing translocations) may maintain or even increase genetic diversity. Our findings underscore the urgent need for active, genetically informed conservation interventions to halt genetic diversity loss.